Secondary Syphilis with Giant Condyloma Acuminatum in Pregnant Women: A Report from a Limited Resource Area - Surya, Raymond; Chelsea, Edelyne; Manurung, Edward Sugito; Banunaek, Diana; Nilasari, Hanny; Saroyo, Yudianto Budi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Introduction: This report shows a case of secondary syphilis in pregnancy with Giant Condyloma Acuminatum (GCA) co-infection DD/condyloma lata which was resolved with alternative treatment of syphilis.Case illustration: A 21-year-old, primigravid woman came to obstetrics outpatient clinic in rural SoE Hospital, East Nusa Tenggara, with a complaint of mass enlargement around vulva (minor and major labia) since 2 months before. Based on Last Menstrual Period (LMP), she was in 34 + 6 weeks of gestation. There were coin lesions in the palms. On genital examination, there was protruded mass sized around 15 x 10 cm, erythematous, and it easily bled on the center part which was suspected to be GCA. Treponema Pallidum rapid (TP-rapid) test using AIM© syphilis rapid test revealed positive results. The patient was diagnosed with secondary syphilis in pregnancy mixed with GCA with dd/condyloma lata and administered Ceftriaxone 1 g intramuscularly once daily for 14 days. She delivered at 41-42 weeks of gestation and a baby girl with 1,980 grams of body weight according to symmetric Intrauterine Growth Restriction (IUGR) was born. No clinical signs of congenital syphilis found.Discussion: Vertical transmission which occurs in each stage of syphilis is related to the presence of spirochetes in the blood circulation. Infants born from syphilis pregnant women consist of 56% of jaundice, 14% of hearing impairment, 8% of renal disease, 8% of mental retardation, and 6% of IUGR or Small for Gestational Age (SGA).Conclusion: Secondary syphilis coinfection with GCA in pregnancy is a rare case report. Syphilis is a significant public health problem globally, especially in Indonesia.Sifilis Sekunder dengan Kondiloma Akuminata Besar pada Wanita Hamil: Sebuah Laporan dari Daerah dengan Keterbatasan Sumber DayaAbstrakPendahuluan: Kasus ini melaporkan sifilis sekunder pada kehamilan dengan kondiloma akuminatum besar dengan koinfeksi dd/kondiloma lata yang beresolusi setelah pemberian tatalaksana alternatif sifilis.Ilustrasi Kasus: Seorang wanita primigravida berusia 21 tahun datang ke poliklinik obstetrik di RSUD SoE, Nusa Tenggara Timur dengan pembesaran massa sekitar vulva (labia minor dan mayor) sejak 2 bulan sebelumnya. Berdasarkan Hari Pertama Haid Terakhir (HPHT), usia kehamilan 34 + 6 minggu. Terdapat lesi pada telapak tangan. Pada pemeriksaan genital, terdapat massa ukuran 15 x 10 cm, eritema, mudah berdarah pada bagian tengah dengan kecurigaan kondiloma akuminatum besar. Hasil tes rapid Treponema Pallidum menggunakan tes rapid sifilis (AIM©) menunjukkan hasil positif. Pasien didiagnosis mengidap sifilis sekunder pada kehamilan dengan kondiloma akuminatum besar dengan koinfeksi dd/ kondiloma lata dan diberikan terapi seftriakson 1 gram intramuscular setiap hari selama 14 hari. Pasien melahirkan saat usia kehamilan 41-42 minggu dan lahir bayi 1.980 gram sesuai dengan Pertumbuhan Janin Terhambat (PJT) simetrik. Tidak ada tanda klinis sifilis kongenital yang ditemukan. Diskusi: Transmisi vertikal dapat terjadi pada setiap tahap sifilis berkaitan dengan keberadaan spiroseta di sirkulasi darah. Bayi lahir dari wanita hamil sifilis biasanya menunjukkan tanda 56% kuning, 14% gangguan pendengaran, 8% gangguan ginjal, 8% retardasi mental, dan 6% PJT atau Kecil Masa Kehamilan (KMK).Kesimpulan: Sifilis sekunder koinfeksi kondiloma akuminatum besar merupakan kasus jarang. Sifilis masih menjadi perhatian kesehatan global, khususnya di Indonesia.Kata kunci: sifilis, koinfeksi, kondiloma akuminatum besar, pertumbuhan janin terhambat